James A. File, 1918. - Unknown (Forsyth County Public Library, 1918)
Source: Booklet, "Winston-Salem, City of Industry," 1918.
James A. File, 1918. Mr. File was proprietor of Electric Shoe Repair Company.
Keywords: Forsyth County (N.C.) -- History -- Sources; Forsyth County (N.C.) -- History -- Pictorial works; Digital Forsyth